Penggunaan Metode Analytic Hierarchy Process Untuk Pembobotan Perilaku Kerja Dalam Penilaian Prestasi Kerja Dosen - Agus Kristianto; Heribertus Ary Setyadi (Paradigma - Jurnal Komputer dan Informatika, 2022)
Assessment of work performance consists of two elements, they are the employee's work goals and work behavior. The assessment of work behavior which consists of service orientation, integrity, commitment, discipline, cooperation and leadership that has been running so far is not considered objective between lecturers who have structural positions and ordinary lecturers. The purpose of this research is to produce a database information system that uses the AHP method to assist leaders in assessing work behavior. Work behavior between lecturers and structural officials will have different weights for some of the behavioral points assessed. AHP method is used to determine the weight of work behavior whose value is generated from the value of the interest ratio that has been entered. Result of this research is the value of work behavior according to the weight of each position and with predetermined criteria.. The system also generates the value of the Tri Dharma Tinggi activities for lecturers which include teaching and education, research, community service and supporting elements. System is made using visual basic programming and has been automated for AHP calculations and the value of lecturer activities. The weights generated by the AHP method are values that are consistent and feasible to use because they have been tested for consistency.